Pengaruh Komposisi Paduan Al-Si Terhadap Kerentanan Hot Tearing - - Akhyar; - Suyitno (Jurnal Teknik Mesin Unsyiah, 2012)
Hot tearing and hot cracking is a metal alloy casting product defects caused by several factors such as alloy composition, casting temperature, mold temperature, mold shape and even casting system itself. The study has been developed to find the phenomenon of the hot tearing by varying the alloy composition, techniques and methods. Increasing Si alloy composition can improve hot-tear, mold modification CRCM (constrained Rod Casting Modified) Horizontal method can be used to analyze the hot tearing. The material used is aluminum with Si composition is 0.24pwt as base and material ADC12 as additive with Si composition is 10.56pwt to increase Si composition. Hot-tearing sensitibility value obtained by using the equation then showing into the chart HTS footprint. HTS values ​​for Si alloy with a composition of 0.24pwt is 12 and the HTS value for alloys with compositions 1.05pwt Si is 18. Cracks formed in the product starting with the smooth (hairline cracks) category to the complete (specimen broken) category. The higher Si content can increase the cracked in product castings, so that the higher Si composition more tendency to tear.